Leishmanicidal and Immunomodulatory Activities of the Palladacycle Complex DPPE 1.1, a Potential Candidate for Treatment of Cutaneous Leishmaniasis - dos Santos, Isabela B. (Front Microbiol, 2018)
The present study focused on the activity of the palladacycle complex DPPE 1.1 on Leishmania (Leishmania) amazonensis. Promastigotes of L. (L.) amazonensis were destroyed in vitro by nanomolar concentrations of DPPE 1.1, whereas intracellular amastigotes were killed at drug concentrations fivefold less toxic than those harmful to macrophages. L. (L.) amazonensis-infected BALB/c mice were treated by intralesional injection of DPPE 1.1. Animals treated with 3.5 and 7.0 mg/kg of DPPE 1.1 showed a significant decrease of foot lesion sizes and a parasite load reduction of 93 and 99%, respectively, when compared to untreated controls. Furthermore, DPPE 1.1 was non-toxic to treated animals. The cathepsin B activity of L. (L.) amazonensis amastigotes was inhibited by DPPE 1.1 as demonstrated spectrofluorometrically by use of a specific fluorogenic substrate. Analysis of T-cells populations in mice treated with DPPE 1.1 and untreated controls was performed by fluorescence-activated cell sorter (FACS). IFN-γ was measured in supernatants of lymphocytes from popliteal and inguinal lymph nodes isolated from treated and untreated mice and stimulated with L. (L.) amazonensis amastigotes extract and active TGF-β was evaluated in supernatants of foot lesions; both dosages were carried out by means of a double-sandwich ELISA assay. A significant increase of TCD4(+) and TCD8(+) lymphocytes and IFN-γ secretion was displayed in mice treated with DPPE 1.1 compared to untreated animals, whereas a significant reduction of active TGF-β was observed in treated mice. These findings open perspectives for further investment in DPPE 1.1 as an alternative option for the chemotherapy of cutaneous leishmaniasis.